Estratégias de escolha de dirigentes públicos no Brasil: alcances e limitações das experiências recentes à luz do debate internacional - Alessio, Maria Fernanda (2017)
This thesis analyzes the selecting and appointing strategies of top public managers in Brazil, debating its advances and limitations in relation to international experiences, in which the managerial competences constitutes a central attribute to the senior civil service models. Its theoretical approach is guided by the international literature on top public managers and senior civil service systems, issues that are insufficiently discussed in Brazil. For this reason, our study clarifies the contours of this theme: it proposes an analytical definition for top public managers and identifies, empirically, in which Brazilian Federal Executive positions they are situated. We argue that the appointment of public managers is preceded by a set of choice mechanisms that are not explored by the brazilian literature, since the existing analyzes, besides not delimiting the managerial space, are based on the dichotomy of the combat to the free appointments associated with the defense of the reserve of positions for servers, without incorporating the attributes of the professional senior civil service. In order to demonstrate the variety of existing choice strategies and overcome this dichotomous view, a broad consultation with federal organizations was made electronically, along with documentary analysis, leading to a categorization of five analytical models, called Discretionary, Conditional, Concertative, Representative and Managerial. Our second argument demonstrates, from a set of documentary analyzes and semi-structured interviews aimed at explaining the emergence of Managerial choices and analyzing its main constituent elements, that this model dialogues with the international debate about top public managers, since its main achievement coincides with its central attribute, oriented to the measurement of managerial competences; its scope, however, is still timid and unrepresentative within the country's federal organizations.